Everybody wants to move—Evolutionary implications of trunk muscle differentiation in vertebrate species. (August 2020) - Lewandowski, Damian; Dubińska-Magiera, Magda; Migocka-Patrzałek, Marta; Niedbalska-Tarnowska, Joanna; Haczkiewicz-Leśniak, Katarzyna; Dzięgiel, Piotr; Daczewska, Małgorzata
Abstract: In our review we have completed current knowledge on myotomal myogenesis in model and non-model vertebrate species (fishes, amphibians, reptiles, birds and mammals) at morphological and molecular levels. Data obtained from these studies reveal distinct similarities and differences between amniote and anamniote species. Based on the available data, we decided to present evolutionary implications in vertebrate trunk muscle development. Despite the fact that in all vertebrates muscle fibres are multinucleated, the pathways leading to them vary between vertebrate taxa. In fishes during early myogenesis myoblasts differentiate into multinucleated lamellae or multinucleate myotubes. In amphibians, myoblasts fuse to form multinucleated myotubes or, bypassing fusion, directly differentiate into mononucleated myotubes. Furthermore, mononucleated myotubes were also observed during primary myogenesis in amniotes. The mononucleated state of myogenic cells could be considered as an old phylogenetic, plesiomorphic feature, whereas direct multinuclearity of myotubes has a synapomorphic character. On the other hand, the explanation of this phenomenon could also be linked to the environmental conditions in which animals develop. The similarities observed in vertebrate myogenesis might result from a conservative myogenic programme governed by the Pax3/Pax7 and myogenic regulatory factor (MRF) network, whereas differences in anamniotes and amniotes are established by spatiotemporal pattern expression of MRFs during muscle differentiation and/or environmental conditions.